THE DISCOURSE OF AMENDMENT N. 95/2016 IN THE CONTEXT OF NEOLIBERAL GOVERNMENTALITY - Barbosa da Silva, Silvia Cristina [UNESP] (2020)
The text presents an analysis on the discourse on the creation of Constitutional Amendment n. 95/2016 in a Foucauldian perspective. The principles of the New Fiscal Regime (NRF) determine a reduction in investments in the health and education sectors. Therefore, we seek to identify the context of the Amendment in the conjuncture of a governmentality that is related to the way subjects are conducted, as well as to point out relations about the emergence of a neoliberal governmentality in which the State tends to be influenced by the private initiative, in the education sector. The proposal of this Amendment is considered biopolitics, because it guides the bodies of the subjects and leads them in the process of their constitution in a relationship of power and control.